MO257: Glucocorticoid Dosing in Induction Remission Treatments for ANCA-Associated Vasculitis. (3rd May 2022) - Floyd, Lauren; Morris, Adam; Shetty, Anamay; Dhaygude, Ajay
Abstract: BACKGROUND: Anti-neutrophil cytoplasm antibodies (ANCA) associated vasculitis (AAV) is a rare and complex autoimmune disease. Induction remission and maintenance treatment typically includes glucocorticoids (GC) in addition to other immunosuppressive medications. Recent trials such as PEXIVAS (1) and ADVOCATE (2) have suggested lower dose GC as induction treatment with no significant detrimental effect on outcomes such as end-stage renal disease (ESRD) or mortality. METHOD: A cohort study of biopsy-proven pauci-immune glomerulonephritis was constructed from a single centre between 2007 and 2021. Retrospective analysis of patients with AAV from a single centre in the North West, UK, compared ESRD and mortality between groups that received high dose versus low dose GC treatment at induction. High dose GC treatment was defined as 1.5 g intravenous (IV) methylprednisolone over 3 days followed by a tapering course of oral prednisolone starting with 60 mg per day. Low dose GC treatment was defined as a single dose of 250 mg pulsed IV methylprednisolone followed by a tapering course of oral prednisolone starting with 30 mg per day. Regression analysis was applied to outcomes including relapse and remission rates, glucocorticoid toxicity index (GTI) and significant adverse events. RESULTS: Fifty-three patients with biopsy-proven ANCA vasculitis were identified. A total of 28 patients received high dose GC induction treatment and 25 patients received a lower dose GC induction regime. The median age for the high dose patients was 68 years (IQR 65–74), which was lower than the low dose patients; 70 years (IQR 58–78). There was a slight (60%) female preponderance in the low dose group compared with a slight male predominance in the high dose group (67%). The Charlson Comorbidity Index (CCI) was completed for all patients. The higher dose cohort had a mean CCI score of 4.8 whilst the lower dose cohort had a lower CCI of 3.8. The number of patients requiring acute dialysis was similar across both the high dose and low dose groups (29% and 32%, respectively). ESRD was also similar between the two groups at 6 months (P = .39). Time to remission was shorter in the lower dose GC cohort (P = .01) and risk of relapse was also reduced (P = .04), as shown in Fig. 1 . Those that received the lower dose GC regime were on less prednisolone at 6 months than those starting with a higher induction dose and this was statistically significant when adjusting for confounders including age, gender and co-morbidities (P = .01). The risk of death was higher in the high dose GC group (21.4% versus 4%, respectively), although this did not reach statistical significance (P = .09). In addition, the risk of adverse events and GC toxicity was higher in the high dose cohort; P = .55 and P = .12, respectively. CONCLUSION: Treatment of ANCA vasculitis remains complex and glucocorticoids remain the cornerstone of induction remission treatment regimes. Whilst our initial data did not show a significant difference in mortality and ESRD outcomes between those that received high versus low dose GC treatment, it demonstrated that low dose GC may be sufficient in the management of AAV. Our small size study suggests a lower dose GC induction remission treatment regime to be safe, effective and associated with fewer adverse effects relating to GC toxicity. Further large studies are needed to look at the narrow therapeutic window of GC and the role of GC-sparing treatments so as to improve outcomes in these patients.